Bat-human interactions and associated factors among communities in Bundibugyo District, Uganda: A cross-sectional study. - James Natweta Baguma; Shamilah Namusisi; Lesley Rose Ninsiima; Rogers Musiitwa; Bridget Nagawa Tamale; Mathius Amperiize; Douglas Bulafu; James Muleme; David Musoke; Clovice Kankya; Charles Drago Kato (PLOS Global Public Health)
More than 70% of new, emerging, and reemerging infectious diseases are from animal origin. Human interaction with bats has been associated as a driver for various fetal zoonoses, including numerous viral diseases of bat-origin. A lot of serological evidence has been gathered around human-bat interaction, yet very little is known regarding the underlying risk factors at community level. This study was aimed at understanding the human-bat interactions and associated factors among communities in Bundibugyo District in Uganda. A cross-sectional study was conducted using both qualitative and quantitative data collection methods in Harugale, Burondo and Ntandi Subcounties in Bundibugyo District between November 2022 and March 2023. A total of 344 participants were interviewed using a structured questionnaire. Key Informant Interviews (KIIs) were also conducted among purposively selected individuals who have vast knowledge on human-bat interaction. Proportional piling and FGDs were conducted among groups of men, women, and youths to get their insights into human-bat interaction. The study revealed that 54.1% of the respondents were males, 42.1% were aged above 40 years. Households headed by males (APR = 1.31, 95% CI:1.07-1.62, Batwa communities (APR = 3.03, 95% CI:1.87-3.94), residing in urban areas (APR = 1.72, 95 CI%:1.35-2.20), trading of food and animal products (APR = 0.6, 95 CI%:0.36-0.99), no occupation (APR = 0.27, 95 CI%:0.12-0.57) and residing in incomplete houses (APR = 1.57, 95 CI%:1.25-1.98) were significantly associated with exposure of humans to bats. There was high exposure of humans to bats in Ntandi compared to Burondo and Harugale. Women groups highlighted use of bat repellants and killing of bats using sticks as the measures to reduce human bat interaction during the focus group discussions (FGDs). Generally, there is high exposure to bats among human communities in Bundibugyo district which increases the risk of zoonotic disease transmission at human-bat interface. Findings from this study aim to enable the one health interventions to reduce bat-human interaction potential risks in both urban and rural areas and support design of feasible interventions for Bundibugyo district and Uganda at large.